Establishing patient-derived organoids from human endometrial cancer and normal endometrium - Katcher, Arielle; Yueh, Brian; Ozler, Kadir; Nizam, Aaron; Kredentser, Ariel; Chung, Charlie; Frimer, Marina; Goldberg, Gary L.; Beyaz, Semir (Frontiers in Endocrinology, 2023)
Endometrial cancer is the most common gynecologic malignancy in the United States and is one of the few malignancies that had an increasing incidence and mortality rate over the last 10 years. Current research models fail to recapitulate actual characteristics of the tumor that are necessary for the proper understanding and treatment of this heterogenous disease. Patient-derived organoids provide a durable and versatile culture system that can capture patient-specific characteristics such as the mutational profile and response to therapy of the primary tumor. Here we describe the methods for establishing, expansion and banking of endometrial cancer organoids to develop a living biobank. Samples of both endometrial tumor tissue and matched normal endometrium were collected from 10 patients. The tissue was digested into single cells and then cultured in optimized media to establish matched patient endometrial cancer and normal endometrial tissue organoids. Organoids were created from all major endometrial cancer histologic subtypes. These organoids are passaged long term, banked and can be utilized for downstream histological and genomic characterization as well as functional assays such as assessing the response to therapeutic drugs.